Interdental cleaning: A cross‑sectional survey of patients attending a tertiary health institution in Nigeria (2015)
Removal of bacterial plaque, the primary etiological factor for periodontal disease, from the oral cavity is one of the modes of preventing this disease, however it is not known if bacterial plaque formed in interdental areas are being cleaned effectively like other tooth surfaces since they are relatively inaccessible. Aim: The aim was to determine the interdental cleaning behavior of patients attending dental clinics of a tertiary health institution in a developing country. A cross‑sectional study in which information such as; tooth surfaces being cleaned regularly, interdental cleaning aids, cleaning frequency, knowledge of interdental cleaning and its source was collected using structured questionnaires from adult patients attending the Dental Centre of the University College Hospital, Ibadan, Nigeria. Data were analyzed using SPSS version 21. Results: A total of 246 patients participated in the study and the mean age was 40.4years (standard deviation =17.4). There were 134 (54.5%) females. Only 86 (35%) were aware of interdental cleaning and 57 (23.2%) practiced it regularly; 39 (15.9%) used dental floss, 12 (4.9%) interdental brushes, 5 (2.0%) wood sticks and 1 (0.4%) used rubber tip stimulators. Two patients used blade and broomstick in addition. The main reason for not cleaning interdentally was no prior knowledge in 160 (65.0%) patients. Conclusion: Less than a quarter of the patients in this study engaged in regular cleaning of the interdental surfaces and lack of knowledge was the major reason for not doing so. Dissemination of information about the importance of interdental cleaning is therefore recommended